PENGARUH VARIABEL EKONOMI DAN SOSIAL DEMOGRAFI TERHADAP STATUS EKONOMI PEREMPUAN DI KABUPATEN JEMBRANA - Krisnawati, Titis; Mahaendra Yasa, I Nyoman (Buletin Studi Ekonomi; VOL.21.NO.1.FEBRUARI.2016 (PP 1-114), 2016)
Abstract : The Influence of Economic and Socio-Demographic Variables to The Woman’s EconomicStatus in Jembrana District. This research was aimed to analyze the influence of economic variables(income, working hours, employment sector, employment status) and socio-demographic variables (areaof residence, number of household members, education level) to the woman’s economic status, eithersimultaneously or partially. The results showed that economic variables (income, working hours,employment sector, employment status) and socio-demographic variables (area of residence, number ofhousehold members, education level) simultaneously have significant influences to woman’s economicstatus in Jembrana. Socio-demographic variables (number of household members) have a significantlypositive effect, meanwhile economic variables (working hours) and socio-demographic variables (levelof education) have a significantly negative effect to the woman’s economic status in Jembrana.Thedominant variable that influence the woman’s economic status in Jembrana is number of household members.   Keywords: economic, socio-demographic, woman economic’s status
Keywords: economic, socio-demographic, woman economic’s status